2014
DOI: 10.1039/c4ra06353h
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial complexation behavior of anionic and cationic cellulose derivatives

Abstract: Study effect of pH values, ionic strength and temperature on assembly behavior of quaternized cellulose and carboxymethyl cellulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Recent studies have shown that, the thickness of poly (L-lysine) (PLL)/hyaluronan (HA) and Cationic starch/ anionic starch film are increases initially with but decreases with higher ionic strength concentration [18,52]. We also showed that the ionic strength dependence of theQC/CMC film thickness differs from that of synthetic polyelectrolyte complex thin films: With increasing the ionic strength, the growth becomes slow when adding 0.5 M NaCl, the thin film growth is almost hindered [40].…”
Section: Influence Of Ionic Strengthmentioning
confidence: 80%
See 3 more Smart Citations
“…Recent studies have shown that, the thickness of poly (L-lysine) (PLL)/hyaluronan (HA) and Cationic starch/ anionic starch film are increases initially with but decreases with higher ionic strength concentration [18,52]. We also showed that the ionic strength dependence of theQC/CMC film thickness differs from that of synthetic polyelectrolyte complex thin films: With increasing the ionic strength, the growth becomes slow when adding 0.5 M NaCl, the thin film growth is almost hindered [40].…”
Section: Influence Of Ionic Strengthmentioning
confidence: 80%
“…The ionic strength of the assemblingsolution was adjusted by adding NaCl. The temperature was controlled by a water bath [40].…”
Section: Thin Film Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…As the ionic strength increases, the film growth is gradually restricted. Increasing the temperature accelerates the thickness growth of the films, but the film becomes rough and the transparency decreases [9] . The main focus of this work is to explore how the operational parameters influence the assembly growth of (CMC) and (QC) thin film.…”
Section: Introductionmentioning
confidence: 99%